BIBLIOGRAFI NASKAH SEJARAH LOKAL: Naskah Riwayat Hidup Abdul Manaf - Rori Afrinaldi; Lidia Maijar (UIN Imam Bonjol Padang, 2023)
This writing explains the life history manuscript of Abdul Manaf or Imam Maulana Abdul Manaf Amin Al-Khatib, who is one of the clerics who adheres to the Syatariyah Order in Koto Tangah, Padang City, and is known for several of his works. Then he wrote and even copied these manuscripts as many as 22 manuscripts, all of which he wrote using Jawi and Arabic script with various texts, such as teaching, history and saga.